Effectiveness of implementation strategies for uptake of fall prevention interventions in community care: A systematic review - Siv Linnerud; Linda Aimée Hartford Kvæl; Birgitte Graverholt; Maria Bjerk; Kristin Taraldsen; Therese Brovold (PLoS ONE, 2025)
Introduction Falls among older adults are one of the leading causes of morbidity and mortality in this population and pose a significant economic burden on society. Despite substantial evidence supporting effective interventions to prevent falls, their uptake in practice remains limited. While various strategies could enhance implementation, few have been evaluated for their effectiveness in fall prevention. This study aimed to assess the effectiveness of such implementation strategies on implementation and health-related outcomes in community care for fall prevention. Method A systematic search was conducted in MEDLINE (Ovid), CINAHL, EMBASE, PsycINFO, Web of Science, the Cochrane Library, and Google Scholar November 27th 2024. We included studies evaluating an implementation strategy for preventing falls among older adults living in the community. Eligible study designs included randomized controlled trials (RCTs), non-randomized trials, controlled before-and-after studies, interrupted time series, and repeated measures studies. The results were narratively synthesized using vote-counting based on the direction of effect. The risk of bias was assessed using RoB2 and ROBINS-I. Results This review identified 8365 distinct references, leading to the inclusion of four articles derived from three unique studies. Our findings suggest that employing a systematic implementation strategy aimed at training and educating stakeholders can enhance the number of fall preventive interventions hosted by counties and communities. However, the results did not indicate a clear direction of effect concerning hospital or emergency department admissions. Conclusion Our review underscores a significant gap in research concerning the effectiveness of implementation strategies for integrating fall prevention interventions into practice. Future research should focus on developing and testing the effectiveness of these strategies in preventing falls among community-dwelling older adults. Registration PROSPERO CDR42022233395.